2017
DOI: 10.1186/s12888-017-1267-5
|View full text |Cite
|
Sign up to set email alerts
|

Possible factors influencing the duration of hospital stay in patients with psychiatric disorders attempting suicide by jumping

Abstract: BackgroundPatients with psychiatric disorders have a high rate of suicide. The present study investigated factors influencing hospital stays for Japanese patients with psychiatric disorders attempting suicide by jumping.MethodsWe diagnosed all suicide attempts (n = 113) by jumping based on the International Classification of Diseases 10th Revision (ICD-10) and investigated the mean hospital stays of patients with each diagnosis based on the ICD-10 code. We then analyzed differences in the demographic and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…However, little is known about socio-demographic and clinical factors associated with LOS in general hospital after violent suicide attempts. Only one recent study investigated these factors among 113 patients having attempted suicide by jumping [20]. The authors reported that LOS was significantly associated with schizophrenia, height of the fall and the number of injuries.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about socio-demographic and clinical factors associated with LOS in general hospital after violent suicide attempts. Only one recent study investigated these factors among 113 patients having attempted suicide by jumping [20]. The authors reported that LOS was significantly associated with schizophrenia, height of the fall and the number of injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Having a diagnosis of schizophrenia, especially among patients without caregivers, was associated with increased LoS. A diagnosis of schizophrenia has consistently been associated with the longest LoS among patients with mental illness [10,12,14,20,38,39]. This is mainly attributed to the severity of the illness and its impact on the perception that hinders individual's functionality outside institutions, such as an increase in criminality [38,40].…”
Section: P-valuementioning
confidence: 99%
“…This is mainly attributed to the severity of the illness and its impact on the perception that hinders individual's functionality outside institutions, such as an increase in criminality [38,40]. Schizophrenia has also been associated with multiple complications such as fractures, malnutrition, and other co-infections (39), all of which may take longer to recover, hence increasing the LoS. The longer LoS among patients with schizophrenia may also be linked to the severe neurocognitive function impairment among patients with schizophrenia that deems them unfunctional outside the hospital environment.…”
Section: P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization states that nearly 800,000 people die each year from suicide, one every 40 seconds [ 1 ]. Most patients who committed suicide had psychiatric disorders [ 2 ]. Among psychiatric disorders, schizophrenia and affective disorders demonstrate the highest risk for suicide [ 3 ], but few studies have examined the differences in the suicide-related features of psychiatric disorders [ 4 ].…”
Section: Introductionmentioning
confidence: 99%